Accelerated 3D multi-channel B 1 + mapping at 7 T for the brain and heart - Kent, James L; de Buck, Matthijs H S; Dragonu, Iulius; Chiew, Mark; Valkovič, Ladislav; Hess, Aaron T (Magnetic resonance in medicine, 2024)
To acquire accurate volumetric multi-channel maps in under 14 s whole-brain or 23 heartbeats whole-heart for parallel transmit (pTx) applications at 7 T. We evaluate the combination of three recently proposed techniques. The acquisition of multi-channel transmit array maps is accelerated using transmit low rank (TxLR) with absolute mapping (Sandwich) acquired in a time-interleaved acquisition of modes (B1TIAMO) fashion. Simulations using synthetic body images derived from Sim4Life were used to test the achievable acceleration for small scan matrices of 24 × 24. Next, we evaluated the method by retrospectively undersampling a fully sampled library of nine subjects in the brain. Finally, Cartesian undersampled phantom and in vivo images were acquired in both the brain of three subjects (8Tx/32 receive [Rx]) and the heart of another three subjects (8Tx/8Rx) at 7 T. Simulation and in vivo results show that volumetric multi-channel maps can be acquired using acceleration factors of 4 in the body, reducing the acquisition time to within 23 heartbeats, which was previously not possible. In silico heart simulations demonstrated a RMS error to the fully sampled native resolution ground truth of 4.2° when combined in first-order circularly polarized mode (mean flip angle 66°) at an acceleration factor of 4. The 14 s 3D maps acquired in the brain have a RMS error of 1.9° to the fully sampled (mean flip angle 86°). The proposed method is demonstrated as a fast pTx calibration technique in the brain and a promising method for pTx calibration in the body.